Psychology of doctor-patient relationship in general medicine - Turabian, Jose Luis (Archives of Community Medicine and Public Health, 2019)
The transcendence of psychological factors of the doctor-patient relationship is given by the fact of its influence on results and quality of medical care, improvement in compliance, satisfaction and recall of physician information, and plays a fundamental role in the medical care process: the skills Listening and communication are fundamental parts to make the diagnosis and treatment. Some of these positive consequences arise from the fact that relationships are linked to emotions which have a physiological substrate. The different psychological behaviors of the patient and the doctor (such as verbal and nonverbal communication, affective behavior, beliefs, empathy, listening), symptom perception, shared decision, negotiation, information, persuasion, etc., give different types of relationship. In doctor-patient relationship there is a modality of psychotherapy, where the treatment is based on that relationship, in which the general practitioner and the patient work together to improve psychopathological conditions through the focus on the therapeutic relationship, which brings consequences on thoughts, emotions, and behaviors. The therapeutic function of the doctor-patient relationship can be understood in analogy to dialysis, in which the patient experience of illness passes through the clinician’s compassionate equanimity for affective detoxification and cognitive clarification. Also, the work of the general practitioner can be understood as a psycho-physiological doctor-patient relationship process through which the doctor and the patient can influence the health of the other. Doctor-patient relationship evaluation has to be carried out jointly by both, doctor and patient, on the effect that both are achieving with that relationship. “The disease is like removing the soil where a tree is planted: the roots are exposed, and you can see how deep and strong they are.” Virginia Woolf (1882-1941; English writer).